2014
DOI: 10.1371/journal.pone.0098749
|View full text |Cite
|
Sign up to set email alerts
|

Skin-Derived Mesenchymal Stem Cells Help Restore Function to Ovaries in a Premature Ovarian Failure Mouse Model

Abstract: Skin-derived mesenchymal stem cells (SMSCs) can differentiate into the three embryonic germ layers. For this reason, they are considered a powerful tool for therapeutic cloning and offer new possibilities for tissue therapy. Recent studies showed that skin-derived stem cells can differentiate into cells expressing germ-cell specific markers in vitro and form oocytes in vivo. The idea that SMSCs may be suitable for the treatment of intractable diseases or traumatic tissue damage has attracted attention. To dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 26 publications
(29 reference statements)
4
59
0
1
Order By: Relevance
“…Previous studies have shown that MSCs can be isolated from many tissues, including skin [37], adipose tissue [10], human amniotic fluid [38], the umbilical cord [39], and the heart [40]. MSCs have become an excellent source of seed cells that can be used for regenerative therapies in a variety of diseases because they have strong self-renewal and multi-differentiation capacities.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that MSCs can be isolated from many tissues, including skin [37], adipose tissue [10], human amniotic fluid [38], the umbilical cord [39], and the heart [40]. MSCs have become an excellent source of seed cells that can be used for regenerative therapies in a variety of diseases because they have strong self-renewal and multi-differentiation capacities.…”
Section: Discussionmentioning
confidence: 99%
“…For example, resveratrol restores ovarian function through inhibiting NF-κB and reducing ovarian inflammation through IL-6 and IL-8 expression [136,137]. Interestingly, recent work has postulated that immune cells and their secreted inflammatory factors follow mechanics to regulate the proliferation and differentiation of ovarian germline stem cells [48,138]. First, immunity may be a part of the OSC niche.…”
Section: Immunosuppressive Mechanisms and Chronic Inflammationmentioning
confidence: 99%
“…Previous studies have shown that MSCs secrete cytokinins, hence, they have a positive effect on proliferation, survival and repair of damaged tissues (Cheng et al, 2013;Ding et al, 2014;Fujita et al, 2004;Wang et al, 2017). Many other previous studies have reported that MSCs implanted into damaged tissues can induce the secretion of bioactive molecules which promote repair of damaged tissues (Lai et al, 2015;Lai, Wang, Dong, & Zhang, 2014;Ranganath, Levy, Inamdar, & Karp, 2012;Schächinger et al, 2006). Likewise, Wang et al (2017) showed that MenSC-derived conditioned media has a significant cytoprotective and anti-apoptotic properties.…”
Section: Previous Mice Model Studies Have Shown That Busulfan Targetsmentioning
confidence: 97%